PCM, nano/microencapsulation and slurries: A review of fundamentals, categories, fabrication, numerical models and applications - Ghasemi, Kasra; Tasnim, Syeda; Mahmud, Shohel (Sustainable energy technologies and assessments, 2022)
•Fundamentals and different characteristic features of PCMs and PCM slurries are explained and compared for various industrial applications.•Compatibility of different core and shell materials along with their plus points and drawbacks are provided.•Available Nano/micro PCM encapsulation fabrication procedures are introduced, and the advantages and disadvantages of each method are highlighted.•Available numerical models for latent heat simulation are presented and the corresponding calculation procedures are described.•Recent advances for Nano/microencapsulated PCM applications in thermal energy storages are reviewed. Sustainable energy is among the ever-increasing concerns in modern society. In this regard, thermal energy storage (TES) working based on latent heat has shown great potential by using phase change materials (PCM) with high heat capacity. However, PCM-TES has several challenges, such as material dispersion, possible chemical reactions with the environment and low thermal conductivity. Embedding PCM in a shell or porous network known as encapsulated PCM (EPCM) in both micro and nano sizes is proposed as a promising solution for these issues. In this study, a state-of-art review of PCM fundamentals, nano/micro EPCM, PCM slurries, coating materials, selection criteria, available fabrication methods, numerical models for latent heat simulation and prominent recent advances is presented. The review has addressed both experimental and numerical studies in detail by providing comparison tables and first of their kind figures. Based on the reviewed articles, chemical encapsulation methods, especially in-situ polymerization, provide a better particle size range and distribution with smooth surfaces, while they cause considerable environmental issues. Moreover, Paraffin wax is the most widely used core material mainly because of its affordability, while inorganic PCM and eutectics are suitable for high-temperature applications and refrigeration, respectively. Among available latent heat simulation models enthalpy-porous and apparent specific heat, that provide capturing solid–liquid interface and ease of use, respectively, are the highly used techniques in different industrial applications. Also, the important subjects and research gaps are detected, and suggestions for future investigations are provided.